Manajemen Lembaga Pengembangan Tilawatil Quran (LPTQ) Kecamatan Medan Area Dalam Pembinaan Qari Dan Qariah - Dalimunthe, Yaqub; Ritonga, Hasnun Jauhari (Universitas Cokroaminoto Yogyakarta, 2025)
This descriptive qualitative research aims to examine the management of the Medan Area District Quran Recitation Development Institute (LPTQ) in the process of coaching qari and qariah. Data collection techniques through interviews, observations, and documentation studies. The research informants include LPTQ administrators, coaches, and fostered participants. The results shows that LPTQ carries out a management process that includes program planning, routine training, and periodic evaluation. The coaching program includes mastery of tajweed, fasohah, vocal techniques, and mental strengthening in preparation for the competition. The support of experienced coaches, synergy with community leaders, and the existence of internal selection events are the driving factors for the success of coaching. However, constraints on funding, facilities and participant motivation are challenges to be resolved. Overall, the management of LPTQ Medan Area District is quite effective in producing outstanding reciters and reciters, although strengthening of resources and innovation is still needed